INTEGRATED COMMUNICATIVE LEARNING APPROACH IN ELP PRACTICE: PRACTICAL APPLICATION IN THE CONTEXT OF INTRA/MULTI/INTER/TRANSDISCIPLINARY INTEGRATION: Practical application in the context of intra/multi/inter/transdisciplinary integration - Ignjatovic, Gordana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
English for Legal Purposes (ELP) or Legal English (LE) is a prominent area of English for Specific Purposes (ESP), catering for the specific discourse community needs and purposes. This article presents the Integrated Communicative Learning (ICL) approach to instructional design within the curricular framework of ELP/LE courses for academic and professional purposes (LEAP/LEPP) in tertiary education. This holistic approach includes ample intradisciplinary, multidisciplinary, interdisciplinary and transdisciplinary dimensions. The first part of this article presents the conceptual, structural and theoretical framework of this approach, and its many pedagogical and methodological functions. The second part outlines the structural framework of the three ELP/LE courses, the teaching/learning context, and the rationale for selecting this approach. The third part focus the practical application of the ICL in these courses, with reference to examples of intra/multi/inter/transdisciplinary integration. Finally, the author discusses the benefits, challenges and considerations in implementing this approach, particularly in view of promoting authentic learning and inter/transdisciplinary legal education